High-strength and air-permeable polymer cement-based waterproof coating and preparation method thereof
Patent Information
- Application Number
- CN202611254871.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]为了解决现有的聚合物水泥基防水涂料,易导致聚合物分子链断裂、涂层粉化、力学性能下降的问题,本申请提供一种高强透气型聚合物水泥基防水涂料及其制备方法
1、由于本申请采用端羟基聚二甲基硅氧烷改性的反应型丙烯酸乳液与水性环氧树脂乳液、潜伏性环氧固化剂共同配合,在涂层中形成化学交联的聚合物网络结构,提升涂层的整体力学性能,采用硫铝酸盐水泥与高活性矿粉共同配合,在涂层中形成梯度水化反应体系,能够减少界面缺陷、提升涂层的致密性,采用微舱自洁增强体将光催化剂封装于其内部,从而在赋予涂层自清洁功能的同时减少光催化剂对聚合物基材的氧化损伤,因此,能够在保持涂层透气性的基础上,同时获得较高的力学强度和稳定的自清洁功能,解决了聚合物水泥基防水涂料,易导致聚合物分子链断裂、涂层粉化、力学性能下降的问题。
Smart Images

Figure CN122898185A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of waterproof coating technology, and more specifically, it relates to a high-strength, breathable polymer cement-based waterproof coating and its preparation method. Background Technology
[0002] Polymer cement-based waterproof coatings, also known as JS waterproof coatings, are two-component waterproof materials composed of organic polymer emulsions, inorganic cement, and fillers. This type of coating combines the flexible film-forming properties of polymer emulsions with the rigid skeleton structure of cement hydration products, exhibiting excellent bonding strength, impermeability, and construction adaptability. It is widely used for waterproofing of building roofs, basements, bathrooms, tunnels, and other projects.
[0003] Currently, polymer cement-based waterproof coatings typically use acrylic emulsions and silicate cement as a compound, and construct physical air-permeable channels by adding porous fillers such as zeolite powder and diatomaceous earth to achieve water vapor permeability of the coating. However, when nano-titanium dioxide is added to give the coating a photocatalytic self-cleaning function, the strong oxidizing free radicals generated by nano-titanium dioxide under light can not only decompose organic dirt on the coating surface, but also indiscriminately attack the polymer emulsion that plays a role in film formation and bonding in the coating, which can easily lead to polymer molecular chain breakage, coating powdering, and decreased mechanical properties. Summary of the Invention
[0004] To address the problems of existing polymer cement-based waterproof coatings, which easily lead to polymer molecular chain breakage, coating chalking, and decreased mechanical properties, this application provides a high-strength, breathable polymer cement-based waterproof coating and its preparation method.
[0005] This application provides a high-strength, breathable polymer-cement-based waterproof coating and its preparation method, which adopts the following technical solution: In the first aspect, this application provides a high-strength, breathable polymer cement-based waterproof coating, which adopts the following technical solution: A high-strength, breathable polymer cement-based waterproof coating comprises the following raw materials in parts by weight: 350-450 parts of hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion, 50-100 parts of waterborne epoxy resin emulsion, 15-30 parts of latent epoxy curing agent, 10-20 parts of composite additives, 300-400 parts of sulfoaluminate cement, 50-100 parts of highly active mineral powder, 3-5 parts of polycarboxylate superplasticizer, and 150-250 parts of micro-chamber self-cleaning reinforcing agent.
[0006] By adopting the above technical solutions, the reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane, combined with waterborne epoxy resin emulsion and latent epoxy curing agent, forms a chemically cross-linked polymer network structure in the coating, improving the overall mechanical properties of the coating. The combination of sulfoaluminate cement and highly active mineral powder forms a gradient hydration reaction system in the coating, which can reduce interface defects and improve the density of the coating. The use of micro-encapsulated self-cleaning reinforcing bodies to encapsulate photocatalysts inside them, thereby giving the coating self-cleaning function while reducing the oxidative damage of photocatalysts to the polymer substrate. Therefore, it is possible to obtain high mechanical strength and stable self-cleaning function while maintaining the air permeability of the coating, thus solving the problems of polymer cement-based waterproof coatings that are prone to polymer molecular chain breakage, coating chalking, and decreased mechanical properties.
[0007] Preferably, the micro-cabin self-cleaning reinforcement has a core-shell-brush three-layer structure, including a core material, a wall material covering the outside of the core material, and a polydimethylsiloxane molecular brush grafted onto the surface of the wall material. The particle size of the micro-cabin self-cleaning reinforcement is 5-20 μm, and its contact angle in water is ≥110°.
[0008] By adopting the above technical solution, the core material is loaded with photocatalyst and photothermal responsive material, the wall material forms a physical isolation barrier, and the surface-grafted polydimethylsiloxane molecular brush gives it low surface energy characteristics, which enables the micro-cabins to migrate to the coating surface to form an enriched layer during the film formation stage. During the use stage, the wall material isolates and prevents the photocatalyst from directly contacting the polymer substrate. The photothermal responsive material triggers the core material to be released on demand. The particle size ensures that the micro-cabins migrate smoothly and form a stable anchoring structure. The contact angle improves the self-cleaning performance of the coating.
[0009] Preferably, the preparation method of the micro-cabin self-cleaning enhancer includes the following steps: Nano-titanium dioxide and ferric oxide nanoparticles with a mass ratio of 9.5-10.5:1 are mixed evenly and then mixed with low-melting-point photocurable epoxy acrylate resin with a melting point of 45-55℃ at a mass ratio of 1:1.8-2.2. The mixture is pre-dispersed at a speed of 1000-1500 rpm for 10-15 minutes and then ultrasonically treated at an ultrasonic power of 400-600 W and a frequency of 20-40 kHz for 20-30 minutes to obtain the core material mixture. Ethyl cellulose is dissolved in an organic solvent to prepare a wall material solution with a mass concentration of 8-12%. The core material mixture and the wall material solution are mixed at a mass ratio of 1:3-1:4 and stirred at 300-500 rpm for 10-15 minutes at 30-40℃ to obtain an oil phase mixture. The oil phase mixture is added to a deionized aqueous solution containing 1-2% polyvinyl alcohol, and stirred at 600-800 rpm for 2-4 hours at 45-55℃. After separation, washing and drying, microcapsule particles are obtained. The volume ratio of the oil phase mixture to the deionized aqueous solution is 1:4-1:6. Hydroxyl-terminated polydimethylsiloxane was dissolved in toluene to prepare a solution with a mass concentration of 5-10%. Microcapsule particles were mixed with the solution at a mass ratio of 1:5-1:8. Dibutyltin dilaurate (0.5-1.0% by mass of hydroxyl-terminated polydimethylsiloxane) was added as a catalyst. The mixture was reacted at 60-80°C for 4-6 hours. After separation, washing, and drying, the self-cleaning microcapsule reinforcer was obtained.
[0010] By adopting the above technical solution, core-shell structured microcapsules are formed by solvent evaporation, and polydimethylsiloxane molecular brushes are introduced through surface grafting reaction to form a complete core-shell-brush three-layer structure. The combination of nano-titanium dioxide and ferric oxide nanoparticles in the core material enables the microcapsule to have both photocatalytic and photothermal response functions. Ethyl cellulose wall material forms an effective physical isolation barrier, and the surface-grafted polydimethylsiloxane molecular brushes endow the microcapsule with low surface energy characteristics and free radical capture ability.
[0011] Preferably, the preparation method of the hydroxyl-terminated polydimethylsiloxane modified reactive acrylic emulsion is as follows: hydroxyl-terminated polydimethylsiloxane and acrylate monomers are subjected to emulsion polymerization in the presence of 1-3% anionic emulsifier and 0.2-0.6% persulfate initiator, with a polymerization temperature of 70-85°C, a reaction time of 3-5 hours, and the solid content is adjusted to 48-52%.
[0012] By adopting the above technical solution, hydroxyl-terminated polydimethylsiloxane is copolymerized with acrylate monomers using emulsion polymerization, so that the polydimethylsiloxane segments are chemically bonded to the acrylate polymer backbone. During the film formation process, the emulsion forms chain segment entanglement with the polydimethylsiloxane molecular brush on the surface of the micro-cabin, enhancing the interfacial bonding force. The reactive hydroxyl-terminated groups in the emulsion chemically crosslink with epoxy resin and cement hydration products, improving the mechanical properties and interfacial stability of the coating.
[0013] Preferably, the glass transition temperature of the hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion is -10°C to -5°C, and the hydroxyl value is 20-30 mg KOH / g.
[0014] By adopting the above technical solution, the glass transition temperature of the emulsion is adjusted to give the emulsion suitable flexibility and film-forming properties. Hydroxyl value control ensures that the emulsion has an appropriate amount of reactive terminal hydroxyl groups, which can undergo chemical cross-linking reaction with epoxy resin and cement hydration products during the coating film formation process to form a stable organic-inorganic composite interface, while avoiding excessively high hydroxyl values that would lead to a decrease in storage stability.
[0015] Preferably, the aqueous epoxy resin emulsion is nonionic, with an epoxy equivalent of 450-550 g / eq and a solid content of 48-52%.
[0016] By adopting the above technical solution, the nonionic waterborne epoxy resin emulsion and the anionic acrylic emulsion system are well compatible. The epoxy equivalent ensures that the epoxy resin has a moderate epoxy group density, forming a moderate cross-linking network. The solid content ensures that the emulsion has suitable viscosity and film-forming properties, which facilitates uniform mixing with the powder components.
[0017] Preferably, the latent epoxy curing agent is a modified amine-ketimine adduct with an amine value of 180-220 mg KOH / g.
[0018] By adopting the above technical solution, a modified amine-ketoimine adduct is used as a latent epoxy curing agent. It has low reactivity with epoxy resin at room temperature, ensuring storage stability. After construction, the ketoimine structure hydrolyzes to release active amine, which initiates the epoxy resin curing reaction. The amine value ensures that the curing agent has a moderate active amine content and fully reacts with epoxy groups to form a three-dimensional network structure.
[0019] Preferably, the composite additive is composed of defoamer, dispersant, wetting agent, and pH adjuster in a mass ratio of 1.8-2.2:2.7-3.3:1.8-2.2:2.7-3.3, and the sulfoaluminate cement is grade 42.5 with a specific surface area of 350-400 m². 2 / kg.
[0020] By adopting the above technical solutions, the defoamer, dispersant, wetting agent and pH adjuster in the composite additives work together to reduce bubbles, promote dispersion, improve wetting and maintain system stability; sulfoaluminate cement ensures that the cement has moderate hydration activity and hydration rate, and forms a gradient hydration reaction system in synergy with highly active mineral powder.
[0021] Preferably, the highly active mineral powder is finely ground blast furnace slag powder with a specific surface area ≥ 400 m². 2 / kg, 7-day activity index ≥75%, 28-day activity index ≥95%, the polycarboxylate superplasticizer is in powder form, with a water reduction rate of 25-30%.
[0022] By adopting the above technical solution, the highly active mineral powder ensures that the mineral powder has high hydration activity. The hydrated calcium silicate gel generated by the secondary hydration reaction fills the interface area. The polycarboxylate superplasticizer reduces the amount of mixing water while ensuring fluidity, thereby improving the density and mechanical strength of the coating.
[0023] Secondly, this application provides a method for preparing a high-strength, breathable polymer cement-based waterproof coating, using the following technical solution: A method for preparing a high-strength, breathable polymer cement-based waterproof coating, applicable to the aforementioned high-strength, breathable polymer cement-based waterproof coating, includes the following steps: The reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane, the waterborne epoxy resin emulsion, the latent epoxy curing agent and the composite additives are dispersed at 300-500 rpm for 15-25 minutes according to the weight ratio, and then filtered through a 180-220 mesh filter to obtain the first component. The second component is obtained by dry mixing sulfoaluminate cement, high-activity mineral powder, polycarboxylate superplasticizer and micro-chamber self-cleaning reinforcement at 500-800 rpm for 10-15 minutes according to the weight parts. Stir the first component at 200-400 rpm, add the second component within 1-2 minutes, and then continue stirring at 300-500 rpm for 3-5 minutes. Let it stand and mature for 2-3 minutes to complete the preparation.
[0024] By adopting the above technical solution, the liquid and powder are prepared separately to ensure storage stability. The dispersion speed and time of the first component are controlled to ensure that the liquid is fully mixed and uniform. Impurities are removed by filtration. The second component is dry-mixed to ensure that the powder is evenly dispersed and to avoid sedimentation and stratification. When mixing for construction, the first component is stirred first, and the second component is slowly added to avoid agglomeration. Stirring is continued to ensure that the coating is fully mixed. Static curing allows air bubbles to escape, resulting in a uniform and workable coating slurry. The operation is simple and the process is controllable.
[0025] In summary, this application has the following beneficial effects: 1. Because this application uses a reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane, combined with a waterborne epoxy resin emulsion and a latent epoxy curing agent, a chemically cross-linked polymer network structure is formed in the coating, improving the overall mechanical properties of the coating. The use of sulfoaluminate cement and highly active mineral powder forms a gradient hydration reaction system in the coating, which can reduce interface defects and improve the density of the coating. The use of micro-encapsulated self-cleaning reinforcement to encapsulate the photocatalyst inside reduces the oxidative damage of the photocatalyst to the polymer substrate while giving the coating a self-cleaning function. Therefore, it can obtain high mechanical strength and stable self-cleaning function while maintaining the air permeability of the coating, thus solving the problem that polymer cement-based waterproof coatings are prone to polymer molecular chain breakage, coating chalking, and decreased mechanical properties.
[0026] 2. This application introduces a micro-cabin self-cleaning enhancer with a core-shell-brush three-layer structure, encapsulating the photocatalyst inside the core material. The wall material forms a physical isolation barrier, and the polydimethylsiloxane molecular brush grafted on the surface drives the micro-cabin to migrate to the coating surface and capture free radicals. This prevents the photocatalyst from contacting the polymer substrate during film formation and the initial stage of use. When surface dirt accumulates, the ferric oxide nanoparticles absorb light energy to trigger the core material to release on demand, thereby achieving a synergistic improvement in self-cleaning function and coating durability.
[0027] 3. This application uses a reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane, an aqueous epoxy resin emulsion, and a latent epoxy curing agent to construct a chemically cross-linked interpenetrating network structure, which enables the coating to have both high strength and good elongation. A gradient hydration reaction system is constructed using sulfoaluminate cement and highly active mineral powder. The hydrated calcium silicate gel generated by the secondary hydration of the mineral powder fills the interface area between the polymer network and the inorganic particles, thereby enhancing the interfacial bonding strength of the coating, improving its impermeability and mechanical properties, while maintaining good air permeability. Attached Figure Description
[0028] Figure 1 This is a flowchart of a method for preparing a high-strength, breathable polymer cement-based waterproof coating provided in this application. Detailed Implementation
[0029] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0030] Technical concept: When existing polymer cement-based waterproof coatings are given self-cleaning function by introducing nano-titanium dioxide photocatalysts, the strong oxidizing free radicals generated by the photocatalysts under light will indiscriminately attack the polymer substrate in the coating, leading to polymer molecular chain breakage, coating chalking and decreased mechanical properties.
[0031] Based on the above findings, this application constructs a micro-chamber self-cleaning reinforcement with a core-shell-brush three-layer structure. This reinforcement is synergistically combined with components such as hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion, waterborne epoxy resin emulsion, latent epoxy curing agent, sulfoaluminate cement, and highly active mineral powder. During the film formation process, the micro-chambers spontaneously migrate to the surface to form a protective layer. During use, the photocatalyst is released on demand through photothermal response. At the same time, the free radical capturing ability of the polydimethylsiloxane molecular brush and the secondary hydration reaction of the highly active mineral powder enhance the interfacial bonding. Thus, while maintaining good air permeability of the coating, it also obtains high mechanical strength and stable self-cleaning function, solving the problems of polymer cement-based waterproof coatings that easily lead to polymer molecular chain breakage, coating chalking, and decreased mechanical properties.
[0032] Unless otherwise specified, all experimental methods used below are conventional methods. All materials, reagents, methods, and instruments used, unless otherwise specified, are conventional materials, reagents, methods, and instruments in this field, which can be obtained commercially or prepared according to literature methods by those skilled in the art.
[0033] Preparation Example 1: Preparation of Micro-cabin Self-Cleaning Reinforcement Nano-titanium dioxide with an average particle size of 25 nm and ferric oxide nanoparticles with an average particle size of 40 nm were mixed at a mass ratio of 10:1. 100 g of the mixed nanoparticles were mixed with 200 g of low-melting-point photocurable epoxy acrylate resin with a melting point of 50 °C. The mixture was pre-dispersed at 1250 rpm for 12.5 minutes and then ultrasonically treated at an ultrasonic power of 500 W and a frequency of 30 kHz for 25 minutes to obtain the core material mixture. Take 100g of ethyl cellulose (viscosity 50mPa·s, ethoxy content 48.5%), dissolve it in 900g of ethyl acetate to prepare a wall material solution with a mass concentration of 10%. Mix 300g of the above core material mixture with 1050g of the wall material solution (mass ratio 1:3.5) and stir at 400rpm for 12.5 minutes at 35℃ to obtain an oil phase mixture. The oil phase mixture was added to a deionized aqueous solution containing 1.5% polyvinyl alcohol, and the volume ratio of the oil phase mixture to the deionized aqueous solution was controlled at 1:5. The mixture was stirred at 700 rpm for 3 hours at 50°C to allow the organic solvent to evaporate completely. After the reaction was completed, the mixture was separated, washed three times with deionized water, and dried in a vacuum drying oven at 45°C for 12 hours to obtain microcapsule particles. 75g of hydroxyl-terminated polydimethylsiloxane (hydroxyl value 20mg KOH / g, viscosity 200mPa·s) was dissolved in 925g of toluene to prepare a 7.5% solution. 100g of the above microcapsule particles were mixed with 650g of PDMS solution (mass ratio 1:6.5), and 0.75% of dibutyltin dilaurate (by mass of hydroxyl-terminated polydimethylsiloxane) was added as a catalyst. The mixture was reacted at 70℃ for 5 hours. After the reaction, the mixture was separated, washed three times with toluene, and then washed once with anhydrous ethanol. It was then dried in a vacuum drying oven at 45℃ for 12 hours to obtain the microcapsule self-cleaning reinforced material.
[0034] Preparation Example 2: Preparation of a reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane Take 300g of methyl methacrylate, 175g of butyl acrylate, and 25g of hydroxyethyl acrylate, mix them evenly to obtain 500g of acrylate monomer mixture, and take 50g of hydroxyl-terminated polydimethylsiloxane (hydroxyl value 20mg KOH / g, viscosity 200mPa·s) and mix it with the above monomer mixture. Dissolve 10g of sodium dodecyl sulfate (2% of the total monomer mass) in 500g of deionized water as an emulsifier solution, and dissolve 2g of ammonium persulfate (0.4% of the total monomer mass) in 50g of deionized water as an initiator solution. In a four-necked flask equipped with a stirrer, thermometer, condenser, and dropping funnel, an emulsifier solution and 200g of deionized water were added. The temperature was raised to 77.5℃. The mixture of monomer and hydroxyl-terminated polydimethylsiloxane was added dropwise to the reaction flask over 2 hours, while an initiator solution was added dropwise. After the addition was complete, the reaction was kept at this temperature for 2 hours. After the reaction was completed, the temperature was lowered to below 40℃, the pH was adjusted to 7-8 with ammonia, the mixture was filtered, and the solid content was adjusted to 50%. The resulting milky white liquid was a reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane.
[0035] Other sources of raw materials: Hydroxyl-terminated polydimethylsiloxane: Commercially available, hydroxyl value 20 mg KOH / g, viscosity 200 mPa·s, manufactured by Dow Corning.
[0036] Acrylic monomers: Methyl methacrylate, butyl acrylate, and hydroxyethyl acrylate are all commercially available industrial-grade products manufactured by BASF.
[0037] Sodium dodecyl sulfate: Commercially available, analytical grade, manufactured by Sinopharm Chemical Reagent Co., Ltd.
[0038] Ammonium persulfate: Commercially available, analytical grade, manufactured by Sinopharm Chemical Reagent Co., Ltd.
[0039] Nano titanium dioxide: Commercially available, anatase type, average particle size 25nm, specific surface area 100m² 2 / g, manufactured by the German company, Seymour.
[0040] Ferric oxide nanoparticles: commercially available, α-Fe2O3, average particle size 40nm, manufactured by Aladdin Reagents Co., Ltd.
[0041] Low melting point UV-curable epoxy acrylate resin: commercially available, melting point 50℃, acid value ≤5mg KOH / g, manufactured by Changxing Chemical Industry Co., Ltd.
[0042] Ethyl cellulose: Commercially available, viscosity 50 mPa·s (5% toluene / ethanol solution), ethoxylate content 48.5%, manufactured by Dow Chemical Company.
[0043] Polyvinyl alcohol: Commercially available, degree of polymerization 1700, degree of alcoholysis 88%, manufactured by Kuraray Co., Ltd. of Japan.
[0044] Dibutyltin dilaurate: Commercially available, analytical grade, manufactured by Aladdin Reagents Co., Ltd.
[0045] Toluene: Commercially available, analytical grade, manufactured by Sinopharm Chemical Reagent Co., Ltd.
[0046] Ethyl acetate: Commercially available, analytical grade, manufactured by Sinopharm Chemical Reagent Co., Ltd.
[0047] Anhydrous ethanol: Commercially available, analytical grade, manufactured by Sinopharm Chemical Reagent Co., Ltd.
[0048] Waterborne epoxy resin emulsion: commercially available, nonionic, epoxy equivalent 500g / eq, solid content 50%, manufactured by Huntsman Corporation, model Araldite PZ 3901.
[0049] Latent epoxy curing agent: commercially available, modified amine-ketoimine adduct, amine value 200mg KOH / g, manufactured by Air Products and Chemicals, model Ancamine 2441.
[0050] Defoamer: Commercially available, polyether-modified silicone, 100% solids content, manufactured by BYK Chemical Company, model BYK-024.
[0051] Dispersant: Commercially available, sodium polyacrylate, 40% solids content, manufactured by BASF, model Dispex AA4040.
[0052] Wetting agent: Commercially available, acetylenol ethoxylate, 100% solids, manufactured by Air Products, model Surfynol 104E.
[0053] pH adjuster: Commercially available, 2-amino-2-methyl-1-propanol, manufactured by Dow Chemical Company, model AMP-95.
[0054] Sulfoaluminate cement: Commercially available, grade 42.5, specific surface area 375 m² 2 / kg, manufactured by Tangshan Polar Bear Building Materials Co., Ltd.
[0055] High-activity mineral powder: Commercially available, finely ground blast furnace slag powder, specific surface area 420 m² 2 / kg, 7-day activity index 78%, 28-day activity index 96%, manufacturer is Shandong Luxin Mining Co., Ltd.
[0056] Polycarboxylate superplasticizer: commercially available, powder, water reduction rate 27.5%, manufactured by Jiangsu Subote New Material Co., Ltd., model PCA-10.
[0057] The unmodified reactive acrylic emulsion used in Comparative Example 7 was commercially available, with a solid content of 50%, a glass transition temperature of -7.5°C, a hydroxyl value of 25 mg KOH / g, and was manufactured by BASF, model Acronal S 505.
[0058] The ordinary slag powder used in Comparative Example 8: commercially available, specific surface area 360 m² 2 / kg, 7-day activity index 62%, 28-day activity index 82%, manufacturer is Hebei Jingye Slag Powder Co., Ltd.
[0059] To better understand the above technical solutions, the technical solutions of the present invention will be clearly and completely described below in conjunction with embodiments.
[0060] The following is a further description with reference to the embodiments: Example 1: Please refer to the appendix Figure 1 A high-strength, breathable polymer cement-based waterproof coating comprises the following raw materials in parts by weight: 400 parts of hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion, 75 parts of waterborne epoxy resin emulsion, 22.5 parts of latent epoxy curing agent, 15 parts of composite additives, 350 parts of sulfoaluminate cement, 75 parts of highly active mineral powder, 4 parts of polycarboxylate superplasticizer, and 200 parts of micro-chamber self-cleaning reinforcing agent.
[0061] The micro-cabin self-cleaning reinforcement has a core-shell-brush three-layer structure, including a core material, a wall material covering the core material, and a polydimethylsiloxane molecular brush grafted onto the surface of the wall material. The particle size of the micro-cabin self-cleaning reinforcement is 12.5 μm, and its contact angle in water is ≥110°.
[0062] The preparation method of the micro-cabin self-cleaning enhancer includes the following steps: After uniformly mixing nano-titanium dioxide and ferric oxide nanoparticles at a mass ratio of 10:1, they were mixed with low-melting-point photocurable epoxy acrylate resin with a melting point of 50℃ at a mass ratio of 1:2. The mixture was pre-dispersed at 1250 rpm for 12.5 minutes, and then ultrasonically treated for 25 minutes at an ultrasonic power of 500 W and a frequency of 30 kHz to obtain the core material mixture. Ethyl cellulose was dissolved in an organic solvent to prepare a wall material solution with a mass concentration of 10%. The core material mixture and the wall material solution were mixed at a mass ratio of 1:3.5 and stirred at 400 rpm for 12.5 minutes at 35°C to obtain an oil phase mixture. The oil phase mixture was added to a deionized aqueous solution containing 1.5% polyvinyl alcohol and stirred at 700 rpm for 3 hours at 50°C. After separation, washing and drying, microcapsule particles were obtained. The volume ratio of the oil phase mixture to the deionized aqueous solution was 1:5. Hydroxyl-terminated polydimethylsiloxane was dissolved in toluene to prepare a 7.5% solution. Microcapsule particles were mixed with the solution at a mass ratio of 1:6.5. Dibutyltin dilaurate (0.75% by mass of hydroxyl-terminated polydimethylsiloxane) was added as a catalyst. The mixture was reacted at 70°C for 5 hours. After separation, washing, and drying, the self-cleaning microcapsule reinforcer was obtained.
[0063] The preparation method of the reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane is as follows: hydroxyl-terminated polydimethylsiloxane and acrylate monomers are emulsion polymerized in the presence of anionic emulsifier accounting for 2% of the total mass of acrylate monomers and persulfate initiator accounting for 0.4%. The polymerization temperature is 77.5℃, the reaction time is 4 hours, and the solid content is adjusted to 50%.
[0064] The glass transition temperature of the hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion is -7.5℃, and the hydroxyl value is 25 mg KOH / g.
[0065] The waterborne epoxy resin emulsion is non-ionic, with an epoxy equivalent of 500 g / eq and a solid content of 50%.
[0066] The latent epoxy curing agent is a modified amine-ketimine adduct with an amine value of 200 mg KOH / g.
[0067] The composite additive consists of defoamer, dispersant, wetting agent, and pH adjuster in a mass ratio of 2:3:2:3. The sulfoaluminate cement is grade 42.5 with a specific surface area of 375 m². 2 / kg.
[0068] The highly active mineral powder is finely ground blast furnace slag powder with a specific surface area ≥400m². 2 / kg, 7-day activity index ≥75%, 28-day activity index ≥95%, polycarboxylate superplasticizer is in powder form, water reduction rate 27.5%.
[0069] A method for preparing a high-strength, breathable polymer cement-based waterproof coating, applicable to the aforementioned high-strength, breathable polymer cement-based waterproof coating, includes the following steps: The reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane, the waterborne epoxy resin emulsion, the latent epoxy curing agent and the composite additive were dispersed at 400 rpm for 20 minutes according to the weight ratio, and then filtered through a 200-mesh filter to obtain the first component. The second component is obtained by dry mixing sulfoaluminate cement, high-activity mineral powder, polycarboxylate superplasticizer and micro-chamber self-cleaning reinforcement at 650 rpm for 12.5 minutes according to the weight parts. Stir the first component at 300 rpm, add the second component within 1.5 minutes, and then continue stirring at 400 rpm for 4 minutes. Let it stand and mature for 2.5 minutes to complete the preparation.
[0070] Example 2: This example differs from Example 1 above in that: A high-strength, breathable polymer cement-based waterproof coating comprises the following raw materials in parts by weight: 450 parts of hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion, 100 parts of waterborne epoxy resin emulsion, 30 parts of latent epoxy curing agent, 20 parts of composite additives, 400 parts of sulfoaluminate cement, 100 parts of highly active mineral powder, 5 parts of polycarboxylate superplasticizer, and 250 parts of micro-chamber self-cleaning reinforcing agent.
[0071] The micro-cabin self-cleaning reinforcement has a core-shell-brush three-layer structure, including a core material, a wall material covering the core material, and a polydimethylsiloxane molecular brush grafted onto the surface of the wall material. The particle size of the micro-cabin self-cleaning reinforcement is 20μm, and its contact angle in water is ≥110°.
[0072] The preparation method of the micro-cabin self-cleaning enhancer includes the following steps: Nano-titanium dioxide and ferric oxide nanoparticles with a mass ratio of 10.5:1 were mixed evenly and then mixed with low-melting-point photocurable epoxy acrylate resin with a melting point of 55℃ at a mass ratio of 1:2.2. The mixture was pre-dispersed at 1500 rpm for 15 minutes and then ultrasonically treated at an ultrasonic power of 600W and a frequency of 40 kHz for 30 minutes to obtain the core material mixture. Ethyl cellulose was dissolved in an organic solvent to prepare a wall material solution with a mass concentration of 12%. The core material mixture and the wall material solution were mixed at a mass ratio of 1:4 and stirred at 500 rpm for 15 minutes at 40°C to obtain an oil phase mixture. The oil phase mixture was added to a deionized aqueous solution containing 2% polyvinyl alcohol and stirred at 800 rpm for 4 hours at 55°C. After separation, washing and drying, microcapsule particles were obtained. The volume ratio of the oil phase mixture to the deionized aqueous solution was 1:6. Hydroxyl-terminated polydimethylsiloxane was dissolved in toluene to prepare a 10% solution. Microcapsule particles were mixed with the solution at a mass ratio of 1:8. Dibutyltin dilaurate (1% by mass of hydroxyl-terminated polydimethylsiloxane) was added as a catalyst. The mixture was reacted at 80°C for 6 hours. After separation, washing, and drying, the self-cleaning microcapsule reinforcer was obtained.
[0073] The preparation method of the reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane is as follows: hydroxyl-terminated polydimethylsiloxane and acrylate monomers are emulsion polymerized in the presence of anionic emulsifier accounting for 3% of the total mass of acrylate monomers and persulfate initiator accounting for 0.6%. The polymerization temperature is 85℃, the reaction time is 5 hours, and the solid content is adjusted to 52%.
[0074] The glass transition temperature of the hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion is -10℃, and the hydroxyl value is 30 mg KOH / g.
[0075] The waterborne epoxy resin emulsion is nonionic, with an epoxy equivalent of 550 g / eq and a solid content of 52%.
[0076] The latent epoxy curing agent is a modified amine-ketimine adduct with an amine value of 220 mg KOH / g.
[0077] The composite additive consists of defoamer, dispersant, wetting agent, and pH adjuster in a mass ratio of 2.2:3.3:2.2:3.3. The sulfoaluminate cement is grade 42.5 with a specific surface area of 400 m². 2 / kg.
[0078] The highly active mineral powder is finely ground blast furnace slag powder with a specific surface area ≥400m². 2 / kg, 7-day activity index ≥75%, 28-day activity index ≥95%, polycarboxylate superplasticizer is in powder form, water reduction rate 30%.
[0079] A method for preparing a high-strength, breathable polymer cement-based waterproof coating, applicable to the aforementioned high-strength, breathable polymer cement-based waterproof coating, includes the following steps: The reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane, the waterborne epoxy resin emulsion, the latent epoxy curing agent and the composite additive were dispersed at 500 rpm for 25 minutes according to the weight ratio, and then filtered through a 220-mesh filter to obtain the first component. The second component is obtained by dry mixing sulfoaluminate cement, high-activity mineral powder, polycarboxylate superplasticizer and micro-chamber self-cleaning reinforcement at 800 rpm for 15 minutes according to the weight parts. Stir the first component at 400 rpm, add the second component within 2 minutes, then continue stirring at 500 rpm for 5 minutes, and let it stand and mature for 3 minutes to complete the preparation.
[0080] Example 3: This example differs from Example 1 above in that: A high-strength, breathable polymer cement-based waterproof coating comprises the following raw materials in parts by weight: 350 parts of hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion, 50 parts of waterborne epoxy resin emulsion, 15 parts of latent epoxy curing agent, 10 parts of composite additives, 300 parts of sulfoaluminate cement, 50 parts of highly active mineral powder, 3 parts of polycarboxylate superplasticizer, and 150 parts of micro-chamber self-cleaning reinforcing agent.
[0081] The micro-cabin self-cleaning reinforcement has a core-shell-brush three-layer structure, including a core material, a wall material covering the core material, and a polydimethylsiloxane molecular brush grafted onto the surface of the wall material. The particle size of the micro-cabin self-cleaning reinforcement is 5μm, and its contact angle in water is ≥110°.
[0082] The preparation method of the micro-cabin self-cleaning enhancer includes the following steps: Nano-titanium dioxide and ferric oxide nanoparticles with a mass ratio of 9.5:1 were mixed evenly and then mixed with low-melting-point photocurable epoxy acrylate resin with a melting point of 45℃ at a mass ratio of 1:1.8. The mixture was pre-dispersed at 1000 rpm for 10 minutes and then ultrasonically treated for 20 minutes at an ultrasonic power of 400W and a frequency of 20 kHz to obtain the core material mixture. Ethyl cellulose was dissolved in an organic solvent to prepare a wall material solution with a mass concentration of 8%. The core material mixture and the wall material solution were mixed at a mass ratio of 1:3 and stirred at 300 rpm for 10 minutes at 30°C to obtain an oil phase mixture. The oil phase mixture was added to a deionized aqueous solution containing 1% polyvinyl alcohol and stirred at 600 rpm for 2 hours at 45°C. After separation, washing and drying, microcapsule particles were obtained. The volume ratio of the oil phase mixture to the deionized aqueous solution was 1:4. Hydroxyl-terminated polydimethylsiloxane was dissolved in toluene to prepare a 5% solution. Microcapsule particles were mixed with the solution at a mass ratio of 1:5. Dibutyltin dilaurate (0.5% by mass of hydroxyl-terminated polydimethylsiloxane) was added as a catalyst. The mixture was reacted at 60°C for 4 hours. After separation, washing, and drying, the self-cleaning microcapsule reinforcer was obtained.
[0083] The preparation method of the reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane is as follows: hydroxyl-terminated polydimethylsiloxane and acrylate monomers are emulsion polymerized in the presence of anionic emulsifier accounting for 1% of the total mass of acrylate monomers and persulfate initiator accounting for 0.2%. The polymerization temperature is 70℃, the reaction time is 3 hours, and the solid content is adjusted to 48%.
[0084] The glass transition temperature of the hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion is -5℃, and the hydroxyl value is 20 mg KOH / g.
[0085] The waterborne epoxy resin emulsion is nonionic, with an epoxy equivalent of 450 g / eq and a solid content of 48%.
[0086] The latent epoxy curing agent is a modified amine-ketoimine adduct with an amine value of 180 mg KOH / g.
[0087] The composite additive consists of defoamer, dispersant, wetting agent, and pH adjuster in a mass ratio of 1.8:2.7:1.8:2.7. The sulfoaluminate cement is grade 42.5 with a specific surface area of 350 m². 2 / kg.
[0088] The highly active mineral powder is finely ground blast furnace slag powder with a specific surface area ≥400m². 2 / kg, 7-day activity index ≥75%, 28-day activity index ≥95%, polycarboxylate superplasticizer is in powder form, water reduction rate 25%.
[0089] A method for preparing a high-strength, breathable polymer cement-based waterproof coating, applicable to the aforementioned high-strength, breathable polymer cement-based waterproof coating, includes the following steps: The reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane, the waterborne epoxy resin emulsion, the latent epoxy curing agent and the composite additives were dispersed at 300 rpm for 15 minutes according to the weight ratio, and then filtered through a 180-mesh filter to obtain the first component. The second component is obtained by dry mixing sulfoaluminate cement, high-activity mineral powder, polycarboxylate superplasticizer and micro-chamber self-cleaning reinforcement at 500 rpm for 10 minutes according to the weight parts. Stir the first component at 200 rpm, add the second component within 1 minute, then continue stirring at 300 rpm for 3 minutes, let stand and mature for 2 minutes to complete the preparation.
[0090] Example 4: This example differs from Example 1 above in that: The particle size of the micro-chamber self-cleaning enhancer is controlled at 8μm, and its contact angle in water is 113°.
[0091] Example 5: This example differs from Example 1 above in that: The composite additive consists of defoamer, dispersant, wetting agent and pH adjuster in a mass ratio of 2.1:2.8:2.1:2.8.
[0092] Example 6: This example differs from Example 1 above in that: The hydroxyl value of the reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane is 22 mg KOH / g.
[0093] Example 7: This example differs from Example 1 above in that: The specific surface area of the highly active mineral powder is 430m². 2 / kg, 7-day activity index 82%, 28-day activity index 98%.
[0094] Comparative Example 1: A polymer cement-based waterproof coating comprising the following raw materials in parts by weight: 400 parts acrylic emulsion, 50 parts water, 5 parts defoamer, 5 parts dispersant, 450 parts silicate cement, 200 parts quartz powder, and 150 parts heavy calcium carbonate powder. The acrylic emulsion has a solid content of 50% and a glass transition temperature of -5℃. The silicate cement is grade 42.5, the quartz powder has a mesh size of 200 mesh, and the heavy calcium carbonate powder has a mesh size of 325 mesh.
[0095] The preparation method is as follows: acrylic emulsion, water, defoamer and dispersant are mixed and dispersed evenly to form a mixture. Silicate cement, quartz powder and heavy calcium carbonate powder are mixed evenly and then mixed with the mixture. The mixture is stirred until uniform, and the product is obtained.
[0096] Comparative Example 2: This comparative example differs from Example 1 above in that: The second component does not contain micro-chamber self-cleaning reinforcement; its weight is supplemented by an equal amount of sulfoaluminate cement.
[0097] Comparative Example 3: This comparative example differs from Example 1 above in that: In the preparation of the micro-cabin self-cleaning reinforcement, there is no microcapsule encapsulation step. The core material mixture is directly dried and pulverized and used as particulate matter, without being encapsulated with ethyl cellulose wall material.
[0098] Comparative Example 4: This comparative example differs from Example 1 above in that: In the preparation of the microcapsule self-cleaning reinforcement, there is no surface molecular brush grafting step, that is, the microcapsule particles are not subjected to PDMS grafting treatment.
[0099] Comparative Example 5: This comparative example differs from Example 1 above in that: The core material of the micro-cabin self-cleaning reinforcement does not contain ferric oxide nanoparticles.
[0100] Comparative Example 6: This comparative example differs from Example 1 above in that: In the preparation of the microcapsule self-cleaning reinforcement, the particle size of the resulting microcapsule particles was controlled to be 50 μm by adjusting the stirring speed during microcapsule encapsulation.
[0101] Comparative Example 7: This comparative example differs from Example 1 above in that: The reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane was replaced with an equal amount of unmodified reactive acrylic emulsion with a solid content of 50%, a glass transition temperature of -7.5℃, and a hydroxyl value of 25 mg KOH / g.
[0102] Comparative Example 8: This comparative example differs from Example 1 above in that: Replacing the highly active mineral powder with an equal amount of ordinary slag powder, the specific surface area is 360m². 2 / kg, 7-day activity index 62%, 28-day activity index 82%.
[0103] Performance testing: The polymer cement-based waterproof coatings prepared in Examples 1-8 and Comparative Examples 1-8 were subjected to the following performance tests: Tensile strength: The coating film was prepared according to GB / T 23445-2025 "Polymer Cement Waterproof Coatings" and its tensile strength (MPa) was determined.
[0104] Elongation at break: The elongation at break (%) of the coating film was determined according to GB / T 23445-2025 "Polymer Cement Waterproof Coatings".
[0105] Water permeability: The water permeability of the coating film under 0.3MPa water pressure for 120 minutes was determined according to GB / T 23445-2025 "Polymer Cement Waterproof Coating".
[0106] Water vapor transmission rate: The water vapor transmission rate of the coating film (g / (m³)) was determined according to GB / T 17146-2015 "Test Method for Water Vapor Transmission Performance of Building Materials". 2 ·24h).
[0107] Water contact angle: The static water contact angle (°) of the coating surface was measured using a contact angle measuring instrument.
[0108] Stain resistance: According to GB / T 9780-2013 "Test method for stain resistance of architectural coatings", the prepared ash is used as the pollution source to determine the stain resistance of the coating (reflection coefficient reduction rate, %). The smaller the value, the better the stain resistance.
[0109] Artificial climate accelerated aging: According to GB / T 23445-2025 "Polymer Cement Waterproof Coatings", the coating film was tested under artificial climate accelerated aging (cumulative irradiation energy 5040kJ / (m²)). 2The appearance and low-temperature flexibility after ·nm).
[0110] Self-cleaning durability: The coating sample was placed in an outdoor natural exposure environment, and the water contact angle was measured every 30 days. The time (days) required for the water contact angle to drop to 90° was recorded.
[0111] The test results are shown in Table 1.
[0112] Table 1
[0113] As can be seen from Example 1 and Comparative Example 2, and Table 1, the micro-cabin self-cleaning reinforcement can achieve a synergistic improvement in coating self-cleaning function and durability. Through its special core-shell-brush three-layer structure, a stable functional layer is formed on the coating surface, which not only endows the coating with excellent self-cleaning performance, but also protects the internal polymer substrate from oxidative damage by photocatalysts. The self-cleaning performance of the coating without this reinforcement is significantly reduced, and the loss of mechanical properties is aggravated after aging.
[0114] As can be seen from Example 1 and Comparative Example 3 and Table 1, the wall material's encapsulation structure can ensure the integrity of the micro-cabin's function. The wall material can effectively encapsulate the photocatalyst inside the micro-cabin, preventing it from directly contacting the polymer substrate during construction and early use, thereby preventing premature photocatalytic oxidation reactions. Without the wall material encapsulation, interface defects appear inside the coating, leading to a decrease in impermeability and a significant reduction in strength retention after aging.
[0115] As can be seen from Example 1 and Comparative Example 4, and Table 1, the polydimethylsiloxane molecular brush can achieve micro-cabin surface migration and free radical capture. The low surface energy of the molecular brush drives the micro-cabin to accumulate on the coating surface during the film formation process, forming a surface protective layer. At the same time, its free radical capture ability can quench the active oxygen generated by the photocatalyst and prevent it from diffusing into the coating. Without the modification of the molecular brush, the surface hydrophobicity and self-cleaning durability of the coating are significantly reduced.
[0116] As can be seen from Example 1 and Comparative Example 5 and Table 1, the photothermal response material can achieve long-term regulation of the self-cleaning function. The material can absorb light energy and convert it into heat energy, triggering the melting and release of the micro-cabin core material, so that the photocatalyst is exposed on the coating surface as needed according to the degree of dirt accumulation, avoiding the activity decay and substrate damage caused by long-term exposure. When the photothermal response material is lacking, the maintenance time of the self-cleaning function is significantly shortened.
[0117] As can be seen from Example 1 and Comparative Example 6, and Table 1, the particle size control of micro-cabins has a significant impact on their migration behavior and surface enrichment effect in the coating. Within the particle size range of this application, micro-cabins can migrate smoothly to the coating surface during film formation and form a stable embedded anchoring structure. When the particle size exceeds the range, the migration of micro-cabins is hindered, the surface enrichment effect is weakened, and the self-cleaning performance and air permeability decrease simultaneously.
[0118] Combined with Examples 1 and 6 and Comparative Example 7 and Table 1, it can be seen that there is a synergistic reinforcing effect between the hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion and the polydimethylsiloxane molecular brush on the surface of the microcapsule. The identical chemical structure of the two causes chain segment entanglement and interfacial crosslinking during film formation, which significantly enhances the interfacial bonding force between the microcapsule and the coating substrate, while improving the overall mechanical properties and anti-aging ability of the coating. When the emulsion is not modified, the interfacial bonding is weakened, and the mechanical properties and the strength retention rate after aging both decrease.
[0119] As can be seen from Examples 1 and 7 and Comparative Example 8, and Table 1, the secondary hydration reaction of highly active mineral powder enhances the density and interfacial bonding of the coating. The mineral powder is activated in the alkaline environment generated by cement hydration, and the resulting hydration products fill the interfacial region between the polymer network and inorganic particles, eliminating weak points at the interface and improving the overall density and impermeability of the coating. When the activity of the mineral powder is insufficient, the interfacial filling effect is weakened, water seepage problems occur in the coating, and the mechanical properties are also affected to a certain extent.
[0120] As can be seen from Examples 1 to 7 and Comparative Examples 1 to 8, and Table 1, this application achieves effective compatibility between photocatalytic self-cleaning function and polymer substrate protection through the dual mechanisms of physical isolation and chemical protection of the micro-cabin. Through the interfacial entanglement between the PDMS modified emulsion and the molecular brush on the surface of the micro-cabin, the organic-inorganic interface is chemically enhanced. Through the secondary hydration reaction of highly active mineral powder, the coating density is further improved. Through the synergistic effect of each component, the coating simultaneously possesses high strength, excellent air permeability, long-lasting self-cleaning, and good aging resistance.
[0121] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high-strength, breathable polymer-cement-based waterproof coating, characterized in that, The raw materials include the following parts by weight: 350-450 parts of hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion, 50-100 parts of waterborne epoxy resin emulsion, 15-30 parts of latent epoxy curing agent, 10-20 parts of composite additives, 300-400 parts of sulfoaluminate cement, 50-100 parts of highly active mineral powder, 3-5 parts of polycarboxylate superplasticizer, and 150-250 parts of micro-cabin self-cleaning reinforcement.
2. The high-strength, breathable polymer cement-based waterproof coating according to claim 1, characterized in that: The micro-chamber self-cleaning reinforcement has a core-shell-brush three-layer structure, including a core material, a wall material covering the outside of the core material, and a polydimethylsiloxane molecular brush grafted onto the surface of the wall material. The particle size of the micro-chamber self-cleaning reinforcement is 5-20μm, and its contact angle in water is ≥110°.
3. The high-strength, breathable polymer cement-based waterproof coating according to claim 1, characterized in that: The preparation method of the micro-cabin self-cleaning reinforcer includes the following steps: Nano-titanium dioxide and ferric oxide nanoparticles with a mass ratio of 9.5-10.5:1 are mixed evenly and then mixed with low-melting-point photocurable epoxy acrylate resin with a melting point of 45-55℃ at a mass ratio of 1:1.8-2.
2. The mixture is pre-dispersed at a speed of 1000-1500 rpm for 10-15 minutes and then ultrasonically treated at an ultrasonic power of 400-600 W and a frequency of 20-40 kHz for 20-30 minutes to obtain the core material mixture. Ethyl cellulose is dissolved in an organic solvent to prepare a wall material solution with a mass concentration of 8-12%. The core material mixture and the wall material solution are mixed at a mass ratio of 1:3-1:4 and stirred at 300-500 rpm for 10-15 minutes at 30-40℃ to obtain an oil phase mixture. The oil phase mixture is added to a deionized aqueous solution containing 1-2% polyvinyl alcohol, and stirred at 600-800 rpm for 2-4 hours at 45-55℃. After separation, washing and drying, microcapsule particles are obtained. The volume ratio of the oil phase mixture to the deionized aqueous solution is 1:4-1:
6. Hydroxyl-terminated polydimethylsiloxane was dissolved in toluene to prepare a solution with a mass concentration of 5-10%. Microcapsule particles were mixed with the solution at a mass ratio of 1:5-1:
8. Dibutyltin dilaurate (0.5-1.0% by mass of hydroxyl-terminated polydimethylsiloxane) was added as a catalyst. The mixture was reacted at 60-80°C for 4-6 hours. After separation, washing, and drying, the self-cleaning microcapsule reinforcer was obtained.
4. The high-strength, breathable polymer cement-based waterproof coating according to claim 1, characterized in that: The preparation method of the hydroxyl-terminated polydimethylsiloxane modified reactive acrylic emulsion is as follows: hydroxyl-terminated polydimethylsiloxane and acrylate monomers are subjected to emulsion polymerization in the presence of 1-3% anionic emulsifier and 0.2-0.6% persulfate initiator, with a polymerization temperature of 70-85℃, a reaction time of 3-5 hours, and the solid content adjusted to 48-52%.
5. The high-strength, breathable polymer cement-based waterproof coating according to claim 1, characterized in that: The glass transition temperature of the hydroxyl-terminated polydimethylsiloxane-modified reactive acrylic emulsion is -10℃ to -5℃, and the hydroxyl value is 20-30 mg KOH / g.
6. The high-strength, breathable polymer cement-based waterproof coating according to claim 1, characterized in that: The aqueous epoxy resin emulsion is nonionic, with an epoxy equivalent of 450-550 g / eq and a solid content of 48-52%.
7. The high-strength, breathable polymer cement-based waterproof coating according to claim 1, characterized in that: The latent epoxy curing agent is a modified amine-ketimine adduct with an amine value of 180-220 mg KOH / g.
8. The high-strength, breathable polymer cement-based waterproof coating according to claim 1, characterized in that: The composite additive consists of defoamer, dispersant, wetting agent, and pH adjuster in a mass ratio of 1.8-2.2:2.7-3.3:1.8-2.2:2.7-3.
3. The sulfoaluminate cement is grade 42.5 with a specific surface area of 350-400 m². 2 / kg.
9. The high-strength, breathable polymer cement-based waterproof coating according to claim 1, characterized in that: The highly active mineral powder is finely ground blast furnace slag powder with a specific surface area ≥400 m². 2 / kg, 7-day activity index ≥75%, 28-day activity index ≥95%, the polycarboxylate superplasticizer is in powder form, with a water reduction rate of 25-30%.
10. A method for preparing a high-strength, breathable polymer cement-based waterproof coating, characterized in that: The high-strength, breathable polymer cement-based waterproof coating according to any one of claims 1-9 comprises the following steps: The reactive acrylic emulsion modified with hydroxyl-terminated polydimethylsiloxane, the waterborne epoxy resin emulsion, the latent epoxy curing agent and the composite additives are dispersed at 300-500 rpm for 15-25 minutes according to the weight ratio, and then filtered through a 180-220 mesh filter to obtain the first component. The second component is obtained by dry mixing sulfoaluminate cement, high-activity mineral powder, polycarboxylate superplasticizer and micro-chamber self-cleaning reinforcement at 500-800 rpm for 10-15 minutes according to the weight parts. Stir the first component at 200-400 rpm, add the second component within 1-2 minutes, and then continue stirring at 300-500 rpm for 3-5 minutes. Let it stand and mature for 2-3 minutes to complete the preparation.